Rediscovering Rubén Darío through translation - Grigsby, CF (2019)
Despite being widely considered one of the most important writers of the Spanish language, Rubén Darío is scarcely known in the English-speaking world. This thesis addresses the question of his obscurity. By approaching Darío’s oeuvre through translation, it sheds light on the history of his reception in English and on the multilingualism of his writing. In addition, it offers new renderings of the modernista’s poetry alongside a critical discussion of the translation of poetry with a view to improving its practice.